Indigenous knowledge in Smart Society 5.0 for Merdeka Curriculum of Elementary School - Gandasari, Adriana; Wahyudin, Dinn; Hernawan, Asep Herry; Supiandi, Markus Iyus; Aristo, Thomas Joni Verawanto; Oktaviani, Ursula Dwi; Selvi, Anastasia; Fiony,; Mawardi, (International Conference on Elementary Education, 2024)
The development of the times and technological advances in the era of society 5.0 cannot be avoided, so a shift in life situations from traditional to modern occurs, and the impact can erode existing indigenous knowledge. This is the basis for conducting research in Sintang Regency, West Kalimantan, Indonesia, which aims to screen existing indigenous knowledge so that it can be preserved by becoming part of the Merdeka curriculum so that it can be implemented at the educational level, one of which is elementary school. This qualitative descriptive research uses a survey with interview methods with primary informants, keys informants, and recommendations informants. The research results show that there are 12 areas of indigenous knowledge with a total of 105 sub-coverages that can be part of the Merdeka curriculum and implemented at the basic education level by utilizing technological collaboration.